1989
DOI: 10.1164/ajrccm/139.5.1158
|View full text |Cite
|
Sign up to set email alerts
|

Impairment after Adult Respiratory Distress Syndrome: An Evaluation Based on American Thoracic Society Recommendations

Abstract: To test the hypothesis that impairment after the adult respiratory distress syndrome (ARDS) is uncommon, we evaluated 41 ARDS survivors using ATS standards for determination of impairment. A total of 101 trials of pulmonary function tests were obtained between 1 and 388 wk after the onset of ARDS. It was possible to evaluate impairment at 1 yr or more after ARDS in 27 subjects. Eighteen of the 27 were impaired. The percentage of ARDS survivors who were impaired on the basis of FVC, FEV1, FEV1/FVC, and DLCOsb w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 9 publications
3
64
0
3
Order By: Relevance
“…It was reported that impairment of pulmonary function, evaluated by spirometric test, can be a relatively common finding in surviving ARDS patients, being present in up to 70% of patients at 1 month [7,39]. However, within the first year, pulmonary function, originally abnormal, can improve, but at 12 months, 20-50% of surviving ARDS patients can still present significant impairment in pulmonary function [4,[7][8][9][10] that usually does not ameliorate thereafter [39].…”
Section: Mortality Rate and Pulmonary Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that impairment of pulmonary function, evaluated by spirometric test, can be a relatively common finding in surviving ARDS patients, being present in up to 70% of patients at 1 month [7,39]. However, within the first year, pulmonary function, originally abnormal, can improve, but at 12 months, 20-50% of surviving ARDS patients can still present significant impairment in pulmonary function [4,[7][8][9][10] that usually does not ameliorate thereafter [39].…”
Section: Mortality Rate and Pulmonary Functionmentioning
confidence: 99%
“…Despite a trend toward better outcome over the years, the mortality rate in ARDS remains above 40% [3], with elevated morbidity [4,5] and social costs [6]. Moreover, it was previously found that surviving ARDS patients may present persistent functional limitation [4,[7][8][9][10] and reduction in healthrelated quality of life (HRQL) [5,[10][11][12][13].…”
mentioning
confidence: 99%
“…[16] One retrospective cohort study (41 people with ARDS) found that duration of mechanical ventilation and severity of ARDS were important determinants of per-sistent symptoms 1 year after recovery. [17] Better lung function was observed when no illness was acquired during the intensive care unit stay, and with rapid resolution of multiple organ failure (e.g. pneumonia during ARDS: 7/41 [17.1%] people with long term impairment v 2/41 [4.9%] with no long term impairment; significance assessment not performed).…”
Section: Prognosismentioning
confidence: 99%
“…pneumonia during ARDS: 7/41 [17.1%] people with long term impairment v 2/41 [4.9%] with no long term impairment; significance assessment not performed). [17] Persistent disability 1 year after discharge from the intensive care unit in survivors of ARDS is secondary to extrapulmonary conditions, most importantly muscle wasting and weakness. [16] Cognitive morbidity: One cohort study (55 people 1 year after ARDS) found that 17/55 (30.1%) exhibited generalised cognitive decline and 43/55 (78.2%) had all, or at least one, of the following: impaired memory, attention, concentration, and decreased mental processing speed.…”
Section: Prognosismentioning
confidence: 99%
“…This fibroproliferative response provokes persistent alveolar consolidation, impaired gas exchange and a severely restrictive pattern on pulmonary function, even after resolution of the edematous phase (13,17 demonstrate a slowly progressive improvement in lung mechanics and gas exchange, which is presumably due to remodelling of the diseased pulmonary parenchyma, with incorporation of the fibrous tissue in the alveolocapillary wall, and opening of new, functional alveolar units ( Figure 2). Indeed, most survivors of ARDS have remarkably few long term alterations in respiratory function (18,19).…”
mentioning
confidence: 99%